Coaches' Perceptions of Common Planning Concepts Within Training Theory: An International Survey - Kechi Anyadike-Danes; Lars Donath; John Kiely (SpringerOpen, 2023)
Abstract Background The planning of training is a popular yet controversial topic among coaches and sports scientists. Periodisation is often presented in the literature as the most efficacious approach to planning training. While historically surveys of coaches appeared to support this a key failing was that no unified definition of periodisation exists. Recent surveys offering a periodisation definition and an alternative planning methodology found many choosing the alternative therefore questioning periodisation's wide acceptance. The current survey looked to explore how coaches perceived specific concepts, drawn from the literature, that relate to the planning of training. Methods 106 coaches [age range: 18-65+ years, 31% 15+ years coaching, 58% individual-events/sports and 32% international level] from across the world completed a novel cross-sectional online survey on the planning of training and the training process. Topics included use of periodisation, division of time into discrete periods, assignment of goals and training to pre-determined periods and the adaptability of pre-established plans. Results The majority described their planning approach as training periodisation (71%). Similarly, there was strong agreement with the necessity to determining a goal for the season (85%) and divide the season into distinct manageable periods of time (73%). When examining whether physical adaptations are achievable within specific and fixed timeframes only a minority (33%) agreed, a similar result was found for training physical capacities in a sequential order (37%). Finally, there was limited support for training targets remaining fixed over a training period (10%). Conclusions As a tool for the planning of athlete's training, periodisation is often presented as the best and most popular approach. Recent research however has highlighted possible discrepancies in its usage among practitioners. The results of this survey echo this and question the acceptance of periodisation concepts even among periodisation users. In part this may be due to key tenets of periodisation no longer being supported by research or practice. A lingering question then is whether the beliefs of coaches, developed through experience and supported by research, will continue to be marginalized. If sports scientists wish to aid coaches then they need to be engaged in future research initiatives as co-collaborators.